Are Major Customers Friends or Masters? Evidence from Customer Fraud Revelations - Banerjee, Shantanu; Dasgupta, Sudipto; Shi, Rui (The Review of Corporate Finance Studies, 2026)
Downstream customer firms’ bargaining power can lead to suboptimal diversification in upstream suppliers’ innovation when customers cannot commit to a long-term relationship. After the revelation of financial fraud by a major customer, suppliers surprisingly outperform a control group in terms of sales growth, Tobin’s q, and survival likelihood over a 10-year period. Our results suggest that, before a fraud revelation, supplier managers’ short decision horizons and aversion to short-term risk enable influential customers to demand relation-specific innovation, leading to suboptimal diversification. When customer importance weakens, suppliers engage in riskier and novel innovation, thereby stimulating sales growth. (JEL G14, G3, L14, L24)